The long alliance : the imperfect union of Joe Biden and Barack Obama - Debenedetti, Gabriel, 1990- (New York : Henry Holt and Company, 2022)
"New York Magazine national correspondent Gabriel Debenedetti reveals an inside look at the historically close, complicated, occasionally co-dependent, and at-times uncertain relationship between Joe Biden and Barack Obama"--
Includes bibliographical references (pages 360-388) and index.
Keywords: Biden, Joseph R., -- Jr. -- Friends and associates; Obama, Barack -- Friends and associates; Presidents -- United States -- Biography; Ex-presidents -- United States -- Biography; Vice-presidents -- United States -- Biography; United States -- Politics and government -- 2001-2009.; United States -- Politics and government -- 2009-2017.; United States -- Politics and government -- 2017-2021.